Peningkatan Disiplin dan Kebersihan Lingkungan Santri Melalui Optimalisasi Peran Kepala Kamar di Pondok Pesantren Putri An-Nur 2 Malang - Hikmah, Alika Aliyatul (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Discipline and environmental cleanliness are two important aspects in shaping students’ character to become resilient, healthy, and responsible individuals. At Pondok Pesantren An-Nur 2, issues related to students’ low discipline in maintaining the cleanliness of their dormitory environment remain a challenge. This Community Service Research (PKM) aims to improve students’ discipline and environmental cleanliness through optimizing the role of room heads as internal agents of change. The method used is a participatory approach involving leadership training, regular mentoring, and the implementation of a reward–punishment system. The results show a significant increase in student discipline and room cleanliness, measured through direct observation and daily assessments over a three-week period. Optimizing the role of room heads has proven effective in encouraging collective behavioral change among students while also strengthening the internal leadership structure within the pesantren environment.